(untitled) (Research, Society and Development, 2021)
In order to know more precisely the wood stock and the structure of native forests, it is very important to identify the existing species and their characteristics. Thus, this work aimed to carry out a forest survey, by simple random sampling, of the floristic composition in an area of the Cerrado biome in the municipality of Bandeirantes, Mato Grosso do Sul. The methodology consisted of the delimitation of five plots of 10 x 100 m, subdivided into 25 areas of 10 x 20 m, the total and commercial height being estimated and the diameter at breast height (≥ 10 cm) of the trees was measured, obtaining the volume of wood, the shaft being classified according to quality (stake, firewood or sawmill). The survey resulted in 395 individuals belonging to 21 families and 49 species. The importance value index (IVI) was calculated for each species, indicating Vochysia tucanorum (Vochysiaceae) as the species with the highest IVI. Fabaceae was the most representative family, with 12 species, followed by Annonaceae, Bignoniaceae and Vochysiaceae, with three species each. The total volume of wood for the area was 3350.64 m3, of which 59.85% of the individuals measured could be destined for the sawmill, demonstrating the potential for use and justifying one of the reasons for the anthropization of this biome.